Avaliação dos efeitos do treinamento do exercício físico aeróbico de curta duração em pacientes hospitalizados com DPOC exacerbado - Knaut, Caroline [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Introduction: Acute Exacerbation (AE) is an important cause of impairment of function in chronic obstructive pulmonary disease (COPD) patients. Negatively affects the quality of life, lung function, muscle weakness, the use of health resources and survival. However, physical exercise performed during the exacerbation can improve the quality of life and the physical capacity of the patient. In this context, this study aims to evaluate the influence of aerobic exercise in hospitalized COPD patients with exacerbation (AECOPD). Objective: To evaluate the effects of short duration aerobic exercise in AECOPD on dyspnea score, quality of life and exercise capacity. Patients and Methods: Twenty-two patients were randomized in two groups; the control group received standard medical treatment and the intervention group that performed aerobic exercise training. All patients performed spirometry, nutritional assessment, distance covered on the six-minute walk test (6MWD), quality of life (Saint George Respiratory Questionnaire- SGRQ), anxiety and depression ( The Hospital Anxiety and Depression Scale), BODE index and intensity of dyspnea (Baseline Dyspnea Index and Modified Medical Research Council Score) after 48 hours of hospitalization and after one month of discharge. The exercise program consisted of aerobic training on a treadmill twice a day for 15 minutes until to the discharge. Results: The impact domain and the total score of quality of life showed a higher increase in the intervention group compared to the control group (p<0.001) when compared to the moments. Both groups showed improvement in the activity domain of SGRQ after one month of hospital discharge, but they did not show difference between groups. Furthermore, only the intervention group showed significant improvement in the symptom domain of SGRQ (p<0.001) and baseline dyspnea index (p=0.006) after one month. 6MWD and BODE did not show difference between ...

Introdução: Exacerbação aguda (EA) é uma importante causa de perda de funções em pacientes que sofrem de doença pulmonar obstrutiva crônica (DPOC). Afeta negativamente a qualidade de vida, a função pulmonar, a fraqueza muscular, a utilização dos recursos da saúde e a sobrevida. Entretanto, o exercício físico realizado durante a exacerbação pode melhorar a qualidade de vida e a capacidade física do paciente. Nesse contexto, o presente estudo visa avaliar a influência da realização do exercício físico em pacientes hospitalizado por exacerbação da DPOC (EADPOC). Objetivo: O presente estudo visa avaliar os efeitos do exercício fisico aeróbio de curta duração nos pacientes hospitalizados por exacerbação aguda de DPOC no escore da dispneia, na qualidade de vida e na capacidade física. Pacientes e Métodos: Vinte e dois pacientes foram randomizados em dois grupos, o grupo controle que recebeu o tratamento clínico padrão e o grupo de intervenção que realizou o treinamento de exercício físico juntamente com os cuidados clínicos. Os pacientes foram submetidos às seguintes avaliações após 48 horas da hospitalização e após um mês da alta: espirometria, avaliação nutricional, distância percorrida no teste de caminhada de seis minutos (DP6), qualidade de vida, ansiedade e depressão, índice de BODE e intensidade de dispneia. O programa de exercício físico foi composto por treinamento aeróbio em esteira ergométrica, duas vezes ao dia, por 15 minutos cada sessão até o período da alta hospitalar. Resultados: O domínio impacto e o escore total da qualidade de vida apresentaram maior incremento no grupo intervenção em relação ao grupo controle (p < 0,001) quando comparado os momentos. Houve melhora de ambos os grupos após um mês de alta hospitalar no domínio atividade quando comparado ao momento basal, mas sem diferença entre os grupos. Além disso, apenas o grupo de intervenção apresentou...
Assessment of the effects of aerobic training short in hospitalized patients with exacerbated COPD: exacerbation; COPD; aerobic exercise
Keywords: Pulmões - Doenças; Pneumopatias obstrutivas; Exercícios respiratórios - Avaliação; Doentes hospitalizados; Lungs - Diseases, Obstructive